2021
DOI: 10.1177/15459683211005020
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin Qigong Improves Balance, Leg Strength, and Mobility in Individuals With Chronic Stroke: A Randomized Controlled Study

Abstract: Background Effective and sustainable exercise training methods for improving balance poststroke are needed. Objective To evaluate the effect of Baduanjin Qigong for improving balance after stroke. Methods This was a single-blinded randomized controlled study in which only the assessor was blinded. Fifty-eight people with chronic stroke (mean age: 62.5 ± 11.8 years) were randomly assigned to the experimental (n = 29) or control group (n = 29). The experimental group underwent 8 weeks of supervised Baduanjin tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Previous studies on the rehabilitation of patients after stroke patients through traditional Chinese exercise have shown that they can enhance the ability of patients to control their trunk as well as leg strength and mobility. Traditional Chinese exercise can also improve the function of respiratory muscles and significantly improve patients’ cognition and quality of life ( Zhang et al, 2016 ; Yuen et al, 2021 ). Meanwhile, in another study on poststroke mind–body problems, acupuncture combined with YYJQE revealed superior improvement effects on the motor function scores and self-rated depression scale scores.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the rehabilitation of patients after stroke patients through traditional Chinese exercise have shown that they can enhance the ability of patients to control their trunk as well as leg strength and mobility. Traditional Chinese exercise can also improve the function of respiratory muscles and significantly improve patients’ cognition and quality of life ( Zhang et al, 2016 ; Yuen et al, 2021 ). Meanwhile, in another study on poststroke mind–body problems, acupuncture combined with YYJQE revealed superior improvement effects on the motor function scores and self-rated depression scale scores.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been due to the multiple movements required for practice of Baduanjin (e.g., weight shifting, trunk rotation, etc.). Several recent studies have investigated the effects of Baduanjin on balance function in patients with neurologic disease such as stroke ( 56 , 57 ) and Parkinson disease ( 58 ). Continued study is needed of the effects of Baduanjin on ecologically relevant functions of balance; for example, crossing an obstacle in real-life situations.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the Baduanjin or Eight-Section Brocades as an example, it consists of eight individual movements and is one of the traditional Chinese Qigong exercise therapies characterized by symmetrical body postures and movements, breathing control, a meditative state of mind, and mental focus [ 25 ]. Baduanjin could effectively improve balance, leg muscle strength, mobility, and fall prevention [ 26 ]. The TBHE intervention process was as follows: (a) The gaps in theoretical knowledge and practical skills in the fall-related lifestyle of older adults was assessed.…”
Section: Methodsmentioning
confidence: 99%